2014
DOI: 10.1021/jp505634q
|View full text |Cite
|
Sign up to set email alerts
|

Discerning Site Selectivity on Graphene Nanoflakes Using Conceptual Density Functional Theory Based Reactivity Descriptors

Abstract: Graphene nanoflakes (GNFs) have more configurational degrees of freedom as compared to Graphene nanoribbons (GNRs) and are viable candidates for future nanodevices. GNFs can be devised with disparate geometries, and their electronic properties can be fine-tuned by genuine chemical functionalization. Hence, it is vital to know specific sites on GNFs where reaction is most feasible for chemical functionalization with donor− acceptor functional groups (nucleophiles/electrophiles). Here, we present spinpolarized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…The optimized geometry of C 42 H 16 surface displays near planarity and the −C−C− bond lengths ∼1.42 Å in good agreement with previous reports . We have examined the binding affinity of nucleobases (A, C, G, and T) on to zigzag‐shaped graphene (C 42 H 16 ) surface . We have initially examined the surface of the graphene by MESP and the nucleobases in figure .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The optimized geometry of C 42 H 16 surface displays near planarity and the −C−C− bond lengths ∼1.42 Å in good agreement with previous reports . We have examined the binding affinity of nucleobases (A, C, G, and T) on to zigzag‐shaped graphene (C 42 H 16 ) surface . We have initially examined the surface of the graphene by MESP and the nucleobases in figure .…”
Section: Resultssupporting
confidence: 83%
“…[45][46][47] We have examined the binding affinity of nucleobases (A, C, G, and T) on to zigzag-shaped graphene (C 42 H 16 ) surface. [48] We have initially examined the surface of the graphene by MESP and the nucleobases in figure 1. The MESP depicts the red region as the negative potential and the blue region depicts the positive potential.…”
Section: Resultsmentioning
confidence: 99%
“…A DFT study carried out by Nazrulla et al on different graphene nanoflake sizes reported that, given a spin state and nanoflake size, the armchair isomer is more reactive than the zigzag isomer. 32 An intensive study carried out by Yu et al on graphene sheets to explore the reactive carbon edge responsible for oxygen reduction reaction (ORR) predicted the armchair edge to more active than the zigzag edge. 33 Another work by Owens showed a gradual decrease in the band gap with the increase in chain length of both armchair and zigzag graphene isomers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…DFT has been extensively used for modeling reactions involving PAHs and calculating their chemical properties (see, e.g., Refs. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] ). The ability of DFT to predict of the relative energies of PAHs and to accurately describe potential energy surfaces involving PAHs is of central importance to many of these studies.…”
Section: Introductionmentioning
confidence: 99%